Association between liver-specific gene polymorphins and their expression levels with nonalcoholic fatty liver disease - Adams, L.; White, S.; Marsh, J.; Lye, S.; Connor, K.; Maganga, R.; Ayonrinda, O.; Olynyk, John; Mori, T.; Beilin, L.; Palmer, L.; Hamdorf, J.; et al. (John Wiley & Sons Inc., 2012)
Genetic factors account for a significant proportion of the phenotypic variance of nonalcoholic fatty liver disease (NAFLD); however, very few predisposing genes have been identified. We aimed to (1) identify novel genetic associations with NAFLD by performing a genome-wide association study (GWAS), and (2) examine the biological expression of the strongest genetic associations in a separate cohort. We performed GWAS of a population-based cohort (Raine Study) of 928 adolescents assessed for NAFLD by ultrasound at age 17. Expression of genes with single nucleotide polymorphisms (SNPs) that were associated with NAFLD at a significance level of P < 10−5 was examined in adults with NAFLD and controls by quantifying hepatic messenger RNA (mRNA) expression and serum levels of protein. After adjustment for sex and degree of adiposity, SNPs in two genes expressed in liver were associated with NAFLD adolescents: group-specific component (GC) (odds ratio [OR], 2.54; P = 1.20 × 10−6) and lymphocyte cytosolic protein-1 (LCP1) (OR, 3.29; P = 2.96 × 10−6). SNPs in two genes expressed in neurons were also associated with NAFLD: lipid phosphate phosphatase-related protein type 4 (LPPR4) (OR, 2.30; P = 4.82 × 10−6) and solute carrier family 38 member 8 (SLC38A8) (OR, 3.14; P = 1.86 × 10−6). Hepatic GC mRNA was significantly reduced (by 83%) and LCP1 mRNA was increased (by 300%) in liver biopsy samples from patients with NAFLD compared to controls (P < 0.05). Mean serum levels of GC protein were significantly lower in patients with NAFLD than controls (250 ± 90 versus 298 ± 90, respectively; P = 0.004); GC protein levels decreased with increasing severity of hepatic steatosis (P < 0.01). Conclusion: The association between GC and LCP1 SNPs and NAFLD as well as altered biological expression implicate these genes in the pathogenesis.